Revision as of 06:23, 4 September 2008 by Thomas34 (Talk)

(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)

Cascading Systems

Problem

Consider two systems:

  • x(t) → 1 → x(t-7)
  • x(t) → 2 → x(2t)

What happens in the following?

a. x(t) → 1 → 2 → ?

b. x(t) → 2 → 1 → ?


Solution to a.

Let's start with a.

Define functions x, y, and z as follows:

x → 1 → y → 2 → z


x(t) → 1 → y(t) = x(t-7)

y(t) → 2 → z(t) = y(2t)

z(t) = y(2t)

y(2t) = x((2t)-7) = x(2t-7).


It may be helpful to consider x(t) = t.

If x(t) = t, then y(t) = x(t-7) = t-7.

If y(t) = t-7, then z(t) = y(2t) = (2t) - 7.

Then, we can simply conclude that since x(2t-7) = 2t-7, z(t) = x(2t-7).


Solution to b.

Next, we move onto b.

Define functions x, y, and z as follows:

x → 2 → y → 1 → z


x(t) → 2 → y(t) = x(2t)

y(t) → 1 → z(t) = y(t-7)

z(t) = y(t-7)

y(t-7) = x(2(t-7)) = x(2t-14).


Again, it may be helpful to consider x(t) = t.

If x(t) = t, then y(t) = x(2t) = 2t.

If y(t) = 2t, then z(t) = y(t-7) = 2(t-7) = 2t-14.

Then, we can simply conclude that since x(2t-14) = 2t-14, z(t) = x(2t-14).


Note

The answers to solutions in a and b are not the same! A cascaded system cannot be freely swapped around and be expected to behave in the same way.

Alumni Liaison

Basic linear algebra uncovers and clarifies very important geometry and algebra.

Dr. Paul Garrett